Distribusi Spasial Logam Berat Besi (Fe) di Perairan Teluk Staring, Sulawesi Tenggara - Bahril, Bahril; Armid, Armid; Jabir, Jabir; Takwir, Amadhan; Rahim, Abdul (ALCHEMY, 2019)
Study on spatial distribution of metal Fe in the coastal area of Staring Bay, Southeast Sulawesi has been carried out. This study aims to determine the spatial distributions of heavy Fe in the coastal area of Staring Bay. Sampling was conducted at 12 stations along the bay through the purposive sampling method. Determination of heavy metal Fe concentration was performed utilizing the Atomic Absorption Spectrophotometry (AAS). Spatial analysis was performed with IDW interpolation method using a software ArcGIS 10.3. The results showed that the concentration of metal Fe at 12 stations was in the range of 0.00187 ppm to 0.01296 ppm whereby the highest level was found at station 7 (mouth of the Laonti river). The spatial analysis in 12 stations confirmed that in the coastal areas of Woru-woru village (near the mouth of the Laonti river) to Gala Island and Wandahea village up to Intan Island have been contaminated by metal Fe ranged from 0.0106-0.0117 ppm and 0.0118-0.013 ppm, respectively. The contamination factor of metal Fe was moderate. Based on the values of CF, the highest contamination of heavy metal Fe is at station 7. Keywords: Spatial analysis, Fe, IDW, CF, Staring Bay  Telah dilakukan studi distribusi spasial logam Fe di perairan Teluk Staring, Sulawesi Tenggara. Penelitian ini bertujuan untuk menentukan sebaran spasial logam Fe di perairan Teluk Staring. Pengambilan sampel dilakukan 12 stasiun di perairan teluk dengan metode purposive sampling. Penentuan kadar logam Fe pada sampel air laut menggunakan Atomic Absorption Spectrophotometry (AAS). Analisis spasial dilakukan dengan metode interpolasi IDW menggunakan software ArcGIS 10.3. Hasil penelitian menunjukkan bahwa kadar logam Fe di 12 stasiun penelitian berkisar antara 0,00187-0,01296 ppm dengan kadar tertinggi berada pada stasiun 7 (muara Sungai Laonti). Hasil analisis spasial pada 12 stasiun menunjukkan bahwa di daerah pesisir Desa Woru-woru (dekat muara Sungai Laonti) hingga Pulau Gala dan Desa Wandahea hingga Pulau Intan telah terkontaminasi logam Fe dengan kisaran 0,0106-0,0117 ppm dan 0,0118-0,013 ppm. Faktor kontaminasi logam Fe bersifat moderat. Berdasarkan nilai CF, kontaminasi tertinggi oleh logam Fe terdapat pada stasiun 7. Kata kunci: Analisis spasial, Fe, IDW, CF, Teluk Staring